2021
DOI: 10.1101/2021.02.04.21250932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The systemic inflammatory response and clinicopathological characteristics in patients admitted to hospital with COVID-19 infection: Comparison of 2 consecutive cohorts

Abstract: Background: In order to manage the COVID-19 systemic inflammatory response, it is important to identify clinicopathological characteristics across multiple cohorts.Methods: Electronic patient records for 2 consecutive cohorts of patients admitted to two urban teaching hospitals with COVID-19 during two 7-week periods of the COVID-19 pandemic in Glasgow, U.K. (cohort 1: 17th March 2020 - 1st May 2020) and (cohort 2: 18th May 2020 - 6th July 2020) were examined for routine clinical, laboratory and clinical outco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
2
2
0
Order By: Relevance
“…Furthermore, large multi-centre cohort studies have shown that a high CFS was independently associated with 30-day mortality [5]. These observations are consistent with recent cohort studies from our own population, that have shown a CFS > 3 was independently associated with 30-day mortality in patients admitted to hospital with COVID-19 [6,7].…”
Section: Introductionsupporting
confidence: 90%
“…Furthermore, large multi-centre cohort studies have shown that a high CFS was independently associated with 30-day mortality [5]. These observations are consistent with recent cohort studies from our own population, that have shown a CFS > 3 was independently associated with 30-day mortality in patients admitted to hospital with COVID-19 [6,7].…”
Section: Introductionsupporting
confidence: 90%
“…Despite the reduction of serum iron in COVID-19-positive patients in this cohort, we did not find important alterations in RBC, hemoglobin or hematocrit, in accordance with previous studies [6][7][8]13,21]. Increased heme was observed in sepsis patients [22] and in murine models of infection [23].…”
Section: Discussionsupporting
confidence: 91%
“…[13] Insensible fluid loss is mainly from cutaneous that is due to constant pyrexia and respiratory that is increased respiratory rates or during intubation due to loss of fluid from mucous and the periciliary fluid by evaporation. [34,35] Dehydration occurring following acute respiratory distress (ARDS) treatment along with the virus disturbs the endocrine function, Wang et al [12] 2021 China 45 64 ± 17.78 66.7 Retrospective ≥146 mmol/L Tzoulis et al [13] 2021 UK 488 68 ± 17.78 56.8 Retrospective ≥146 mmol/L Trecarichi et al [14] 2020 Italy 50 80 ± 12 57.1 Retrospective >145 mmol/L Sjöström et al [31] 2021 Sweden 406 59 ± 12.3 75 Retrospective ≥145 mmol/L Sjöström et al [32] 2020 Sweden 223 59 ± 2.37 79.37 Retrospective ≥145 mmol/L Ruiz-Sanchez et al [15] 2020 Spain, Italy Cuba, Ecuador Germany, China, and Canada 4664 66 ± 18.51 58 Retrospective >145 mmol/L Maniero et al [16] 2021 UK 124 83 ± 7.22 50.8 Retrospective NA Maguire et al [17] 2021 UK 261 66%>70 46 Prospective >146 mmol/L Asghar et al [18] 2020 Pakistan 373 52.78 ± 15.76 67.02 Prospective >145 mEq/L Atila et al [19] 2021 Switzerland Cases: 172 Control:849 59 ± 22.96 55 Prospective >147 mmol/L Berni et al [20] 2021 Italy 380 67.53 ± 15.48 61.57 Prospective >145 mEq/L Duan et al [21] 2020 China 348 44.8 ± 15 47.12 Retrospective >138 mmol/L Hirsch et al [22] 2021 USA 9946 71 ± 14.07 59.39 Retrospective >144 mEq/L Hu et al [23] 2021 China 1254 56 ± 55.5 51.1 Retrospective >145 mmol/L Longhitano et al [24] 2021 Italy 115 73 ± 60.74 55 Prospective >145 mmol/L Wu et al [26] 2020 China 125 55 52.8 Retrospective >145 mmol/l Sarvazad et al [25] 2020 Iran 58 56 57 Prospective >146 meq/L like Renin-angiotensin-aldosterone system, expecting to shift the electrolyte pattern to hypernatremia. [31] Contrary to physiological phenomena, despite the administration of diuretics (leading to sodium excretion) and despite the administration of free water, plasma sodium level remains raised.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a more pronounced and much higher incidence of hypernatremia in COVID-19 patients, pointing to the fact that hypernatremia can be a manifestation of COVID-19, generally seen to be associated with adverse outcomes. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] With a surge in such publications related to the prevalence and impact of hypernatremia in COVID-19 patients, our primary objective was to examine the association of elevated serum sodium with key clinical outcomes, including mortality, ventilation, intensive care unit (ICU) admission and prolonged hospital stay.…”
Section: Introductionmentioning
confidence: 99%